Membrane-interacting properties of the functionalised fatty acid moiety of muraymycin antibiotics1. Issue 5 (13th May 2015) - Ries, Oliver; Carnarius, Christian; Steinem, Claudia; Ducho, Christian
<x xml:space="preserve">Abstract</x> A simplified model system is introduced to elucidate the significance of the ω-functionalised fatty acid moiety of muraymycin nucleoside antibiotics for membrane interaction and penetration.